Determinantes sociales que condicionan la actividad sexual precoz de los adolescentes - Fernández Tapia, Sonia (2020)
Objective. To analyze the social determinants that condition early sexual activity of adolescents. Methods. Quantitative, descriptive, explanatory and cross-sectional study. The sample comprised 254 students between 14 and 18 years of age. A questionnaire was applied to them. It evaluated the personal, family and contextual dimensions and the initiation of sexual activity. For the analysis of the relationship between variables, chi-square statistical test and multiple linear regression model were used. Results. Personal conditioning factors, age of sexual initiation, lack of contraceptive use, and little knowledge of the signs and symptoms of sexually transmitted infections were identifed. Among determinants related to their families, level of education of their parents, support from their mothers, and verbal and physical violence appearto have a signifcant association. Along with the lack of habit of going to health services, television programs and friends appear as the ones that most promote the initiation of early sexual activity. Conclusions. Personal, family and contextual are determinants that signifcantly inﬂuence initiation of adolescent sexual activity, aﬀecting their sexual and reproductive health.